Impact of the first year of the "This Girl Can" physical activity and sport mass media campaign in Australia - Adrian Bauman; Nicola McNeil; Matthew Nicholson; Paul O'Halloran; Emma Seal; Erica Randle; Arthur Stukas (BMC, 2023)
Abstract Introduction Addressing gender inequalities in physical activity is an important public health goal. A major campaign, 'This Girl Can' (TGC) was conducted by Sport England from 2015, and TGC was licenced in 2018 by VicHealth in Australia for development and use in a 3-year mass media campaign. The campaign was adapted through formative testing to Australian conditions and implemented within the state of Victoria. The purpose of this evaluation was to assess the initial population impact of the first wave of the TGC-Victoria. Methods We assessed campaign impact using serial population surveys, with the target population being women living in Victoria who were not meeting the current physical activity guidelines. Two surveys were carried out before the campaign (October 2017 and March 2018), and the post-campaign survey immediately following the first wave of TGC-Victoria mass media (May 2018). Analyses were primarily on the cohort sample of 818 low-active women followed across all three surveys. We measured campaign effects using campaign awareness and recall, and self-report measures of physical activity behaviour and perceptions of being judged. Changes in perceptions of being judged and in reported physical activity were assessed in relation to campaign awareness over time. Results Overall, TGC-Victoria campaign recall increased from 11.2% pre-campaign to 31.9% post-campaign, with campaign awareness more likely among younger and more educated women. There was a slight increase of 0.19 days in weekly physical activity following the campaign. Feeling that being judged was a barrier to physical activity declined at follow up, as did the single item perceptions of feeling judged (P < 0.01). Feeling embarrassed decreased, and self-determination increased, but exercise relevance, theory of planned behaviour and self-efficacy scores did not change. Conclusions The initial wave of the TGC-Victoria mass media campaign showed reasonably high levels of community awareness and encouraging decreases in women feeling judged whilst being active, but these did not yet translate into overall physical activity gains. Further waves of the TGC-V campaign are in progress to reinforce these changes and further influence the perception of being judged among low-active Victorian women.